PENDIDIKAN TRANSFORMATIF: TANTANGAN DALAM MENINGKATKAN MUTU DAN KOMPETENSI GURU SMA/MA/SMK DI BANYUWANGI - Hikmah, Siti Nur Afifatul; Nurhayati, Aini; Hasbullah Ridwan, Muhammad; Ma’arif, Moh. Syamsul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Transformative learning creates changes in an individual's perspective, making individuals more mature and mature in thinking and acting, based on cognitive, rational, affective and affective processes, as well as communicative and social aspects which aim to make a person smarter and more critical. The importance of teacher competence and quality in the world of education has a big influence on student success. This research aims to determine the role and innovation of transformative education in improving quality and competence as well as transformative education strategies in improving the quality and competence of SMA/MA/SMK teachers in Banyuwangi. This research uses qualitative research methods with the type of microethnography. The data collection techniques used include participant observation, structured interviews, qualitative notes, and documentation. Researchers used data analysis using the Miles Huberman flow with four stages including; data collection, data reduction, concluding research data, and data verification. Research states that teachers must be able to improve the quality and competence of education along with changing times. Changes in education can begin with the presence of teachers who are qualified and able to have competitiveness in terms of quality and competence.